Right of Issuing Bank to be Subrogated to the Applicant of Letter of Credit Under the Insurance Contracts - Al-Daboubi, Derar (2022)
This article discusses the case where the efforts of the issuing bank prove futile to recovering the payment - paid to the beneficiary - from the applicant of the letter of credit. In particular, when the sold goods - the subject matter of the letter of credit - received damaged or lost. This scenario is envisaged when the applicant refuses to make the payment imposed under the letter of credit. The necessity of discussing this matter is to clarify whether or not the issuing bank can be subrogated to the beneficiary’s rights acquired under insurance contract. The analysis will focus on the English law and Uniform Customs & Practice for Documentary Credits (UCP600), in order to illuminate the legal grounds on which the issuing bank can stand so as to enjoy such rights, through which the paid fund can be reimbursed.